Dravidacris annamalaica gen. et sp. nov. a new pygmy unicorn grasshopper (Orthoptera: Tetrigidae) from South India - Bhaskar, Dhaneesh; Sankararaman, H.; Kasalo, Niko (Zootaxa, 2022)
A new pygmy unicorn genus, Dravidacris Bhaskar et Kasalo, gen. nov., and its single species D. annamalaica Bhaskar et Kasalo sp. nov. are described, restricted to the Eastern coast of Tamil Nadu, one of the southern states of India. Dravidarcis gen. nov. is a unique pygmy grasshopper genus with its long, elevated, and projected vertex. Long and dorsally extended flat fastigium of Dravidacris gen. nov. is similar to that of Pseudomitraria from Africa, Rostella from SE Asia, and Indomiriatra from India. However, those species are different and are not closely related. The new genus is easily separated from the genera mentioned above by the shape of the horn, the way the horn is developed, the expression of medial and median carinae, and the shape of the anterior margin of the pronotum. The implications of differing horn morphologies are discussed, and some taxonomic comments are offered.